(untitled) (Journal of Hama University, 2021)
Introduction: Nasogastric tube (NGT) feeding is considered a good and popular nutritional method for patients in the(Intensive Care Unit) ICU. It is essential that the nursing staff have a correct performance and a good basic knowledge of the components of feeding support and the feeding procedure via NGT. Aim of the study was to identify the level of nursing staff knowledge and performance in the NGT feeding procedure. Methods: A descriptive study was conducted on all nurses in the ICU, reaching 34 nurses at Tishreen University Hospital in Lattakia. Using two tools knowledge questionnaire and chick list by the researcher developed. Results: The Findings showed that half of the of the nurses 50% have a moderate level of knowledge, and the majority of the nurses 82.4%, performed poorly in the nutritional procedures via NGT. Recommendations: This study recommended educational and training sessions for ICU’s nursing staff on NGT nutrition. There is need to regular and continuous evaluation of the knowledge and performance of the nursing staff during enteral feeding, and a study on a larger sample that includes several hospitals to confirm the results of the study in order to generalize the results.